Cryo comminution of food waste. Issue 1 (2014) - B.S. Sridhar
<x xml:space="preserve"> Abstract </x> Purpose – The present study involved the development of a value‐added comminution process for different recycled meat processing by‐products such as bones for management of waste products. The paper aims to discuss these issues. Design/methodology/approach – An indigenous cryo‐grinding system was developed and pilot scale comminution tests were carried out on goat and hen bones under different temperature conditions ranging between −15°C and −40°C and sample pre‐conditioning adopting liquid nitrogen as a grinding medium. Findings – Cryo comminution produces finer, uniform particle sizes, increased specific surface area per unit mass with lesser specific energy consumption in comparison to room temperature comminution. Breakage behavior studies showed that hardness (609‐685 MPa) and brittleness (24‐29 m−1/2) and strain energy decreased (3.1‐1.1 N‐m) as the temperature was lowered. Weight mean diameter, specific energy consumption under ambient and cryogenic conditions, respectively, were 125 and 80 μm, 1, 303 and 1, 108 kJ/kg. The process developed attempts to eliminate environmental pollution by reducing food wastes generated and incorporates value to waste products. Originality/value – A value‐added comminution process for meat processing by‐products such as bones was developed to reduce food wastes generated as well as environmental pollution. The process aims to improve public health stressing the importance of recycling through the management of food waste products. Public and private organizations can act as profit centers generating significant revenue and employment by adopting the process.